Table of Content - -, (Arab Journal for Sciences and Research Publishing, 2024)
Table of Content:1. The Use of Generative Artificial Intelligence in Graduate Studies Research: A Case StudyMr. Turki Mohammed Habkoor Almoharraq2. The problem of complexity and Consistency in the intelligence cycle: A critique of the effects of structural and dynamic interactions on intelligence efficiencyDr. Mohamed Elzin Mohamed Ahmed Ibrahim3. Evaluation of the Governance of the National Initiative for Human Development and Its Impact  on Territorial Development in Morocco's Eastern Rif from 2005 to 2024: A Case Study of the Oulad Zbair and Beni Frassen CommunitiesMr. Mohamed El-Fazziki, Ms. Fatima Ghmimed, Dr. Jawad El-Bazwi, Dr. Abdelouahed Bouberria4. The Big Five factors of personality model: A study of history, evolution, and areas of application in the digital contextDr. Reda El-Yazidi5. Draft proposal to facilitate the receipt and kissing of black stone for pilgrims and worshipersDr. Mohamed Hanafy Abdullah Morsy6. Economic relations between The Extremity Maghreb and Western Sudan during The Eighth Century AH, Fourteenth century AD.Dr. Assadik Ahmad Adam., Dr. Mahamat Saleh Daway
Keywords: Arab Journal of Sciences & Research Publishing